2005
DOI: 10.1001/archinte.165.20.2402
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Related Functioning in a Traumatized Community

Abstract: Up to 4 years after the disaster, symptoms were more prevalent among survivors than controls. Although medical disorders cannot be excluded, the reported symptoms showed several features similar to those of medically unexplained symptoms in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…4-6 Chronic pain is associated with increased stress and an impaired ability to cope effectively with stressful life events. 7 Patients with concomitant pain, anxiety, and social stressors are more likely to report greater depressive symptoms. Similarly, the likelihood of an anxiety disorder increases among individuals who experience pain and are also faced with social stressors.…”
Section: Introductionmentioning
confidence: 99%
“…4-6 Chronic pain is associated with increased stress and an impaired ability to cope effectively with stressful life events. 7 Patients with concomitant pain, anxiety, and social stressors are more likely to report greater depressive symptoms. Similarly, the likelihood of an anxiety disorder increases among individuals who experience pain and are also faced with social stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Pain may be associated with increased stress, and reduced resilience and coping capability when faced with stressful and traumatic life events [12]. Living with pain can lead to social isolation, interrupted ability to maintain roles such as grocery shopping and child care, and increased dependence on others for support.…”
Section: Introductionmentioning
confidence: 99%
“…In past studies, disaster victims have scored higher than norms or controls on objective measures of morbidity (Holen 1991;Palinkas et al 1993), as well as on self-reported somatic complaints or checklists of medical conditions (e.g., Clayer et al 1985;Murphy 1984;Norris et al 2006;Phifer et al 1988). In particular, research has shown that physical health is negatively affected regardless of whether the disasters were natural or human-caused, and is particularly compromised for victims who were forced to relocate after the disaster (Escobar et al 1992;van den Berg et al 2005).…”
Section: Introductionmentioning
confidence: 99%